KANDUNGAN BAHAN KIMIA OBAT PADA OBAT TRADISIONAL YANG BEREDAR DI PASARAN - PertiwI, Putu Larassita Abdi; Suariyani, Ni Luh Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 7 No 2 (2020): Desember 2020DO - 10.24843/ACH.2020.v07.i02.p08, 2020)
ABSTRACT Traditional medicine such as herbal medicine is still widely used in Indonesia, there are many types of traditional medicine that currently appear on the market. In 2018 there are 135 drug industries in Indonesia. Many traditional medicine in market, it makes difficult to control the traditional medicine industry that does not apply CPOTB (Good Manufacturing Practices of Traditional Medicine) in the production process of traditional medicines. The purpose of this research is to find out how the description of the use of medicinal chemicals in various traditional medicinal products. Data collection method used is by collecting secondary data. By using univariate data analysis techniques. Results: Based on the results of data analysis it was found that there had been a decline in traditional medicine with medicinal chemicals. The highest content of chemicals is found in traditional medicines that have the efficacy of Male Stamina Herbs. Many medicinal chemicals that are still found are: Sildenafil Citrate, Paracetamol, Dexamethason, CTM, Na Diclofenac, Fenibutason, Piroxikam, Sibutramin HCL. Decreasing the use of traditional medicines with medicinal chemicals it’s mean there are still traditional medicines that use medicinal chemicals by traditional medicine There are still many people who are interested in the faster effects that are given. By traditional medicine, will have a harmful effect on the body. Therefore, it a chance for the industrial to ad medicine chemical into their traditional medicine. However, commounity do not have enough knowledge that consume that kind of medicine continously.